1993
DOI: 10.1161/01.atv.13.12.1790
|View full text |Cite
|
Sign up to set email alerts
|

Influence of probucol on enhanced LDL oxidation after fish oil treatment of hypertriglyceridemic patients.

Abstract: The susceptibility of low-density lipoprotein (LDL) to oxidation was studied in hypertriglyceridemic men (5 with type III and 5 with type IV) at baseline on a low-saturated-fat, low-cholesterol diet, after 6 weeks of dietary supplementation with fish oil (Promega, 12 g/d), and after 6 weeks of fish oil combined with probucol (500 mg BID). The relative content of n-3 polyunsaturated fatty acids in plasma and LDL was increased during the two treatment periods, and a low a-tocopherol to n-3 polyunsaturated fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 47 publications
2
14
0
1
Order By: Relevance
“…However, these studies may have been underpowered due to the relatively large analytical variance of the assays that they employed. Other studies also using alternative methods found similar to us a decreased resistance of LDL to oxidation (Lussier-Cacan et al, 1993;Suzukawa et al, 1995;Higdon et al, 2001). Studies in which plasma concentrations of lipid peroxidation products were determined as a measure for in vivo lipid peroxidation found either no change or increased peroxidation after fish oil consumption.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, these studies may have been underpowered due to the relatively large analytical variance of the assays that they employed. Other studies also using alternative methods found similar to us a decreased resistance of LDL to oxidation (Lussier-Cacan et al, 1993;Suzukawa et al, 1995;Higdon et al, 2001). Studies in which plasma concentrations of lipid peroxidation products were determined as a measure for in vivo lipid peroxidation found either no change or increased peroxidation after fish oil consumption.…”
Section: Discussionsupporting
confidence: 79%
“…Fish oil supplementation and LDL H Pedersen et al no effect of fish oil on plasma TBARS, while others showed increased plasma TBARS concentrations after fish oil supplementation (Lussier-Cacan et al, 1993;Suzukawa et al, 1995;Tsai & Lu, 1997). Higdon et al (2000) found no effect of fish oil supplementation on plasma MDA in nondiabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the atherogenic potential of oxidized LDL in man, an increase in LDL oxidation by fish oil in vivo may tend to diminish the overall anti-atherogenic effect of fish oil. Coadministration of probucol has been shown to prevent LDL oxidation by fish oil (Lussier-Cacan 1993) and Drevon (1992) suggests that the potential of high n-3 PUFA intakes to oxidize lipids may increase the requirement for Vitamin E. Thus addition of adequate amounts of Vitamin E or other antioxidants to the fish oil supplements may be necessary to offset this potentially adverse effect.…”
Section: Other Considerationsmentioning
confidence: 99%
“…There was no reduction of arachidonic acid in plasma nor in LDL. Suzukawa [5], in hypertensive subjects, and LussierCacan [38], in hypertriglyceridaemic subjects, found a decrease in arachidonic acid in LDL, but n-3 PUFA intake was higher and supplementation duration was longer (3.4 and 4.8 g/day n-3 fatty acids for 6 and 8 weeks, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, vitamin E supplementation has been shown to counteract the ®sh oil-induced increase in LDL oxidizability [29,44]. Panzetta & Lussier-Cacan observed the same effects, but their ®sh oil preparation contained retinol with vitamin E [45] or probucol [38].…”
Section: Discussionmentioning
confidence: 99%